THE EFFECTIVENESS OF VOCABULARY-BASED-INTEGRATED ACTIVITIES IN IMPROVING THE STUDENTS’ VOCABULARY COMMAND - Andi Haeriati Alimuddin (Universitas Negeri Makassar, 2015)
Finding a method to be used in vocabulary teaching and learning for students with different learning style is a big challenge for English teachers at SMA Negeri 1 Soppeng Riaja as the result of preliminary study found that the students’ vocabulary command is still low and the teacher promoted less awareness of students’ learning styles in vocabulary learning. An exploratory research was conducted to investigate the effectiveness of Vocabulary-based Integrated Activities in improving the students’ vocabulary command by involving the second year students of natural science class of SMA Negeri 1 Soppeng Riaja in academic year 2012/2013. It is concluded from quantitative and qualitative findings that the Vocabulary-based Integrated Activities are: (1) most effective to improve the students’ vocabulary command in terms of knowing, understanding the words and how they are said and written; (2) most effective to improve the students’ vocabulary command in terms of using the words in written form; (3) effective to improve the students’ ability the students’ vocabulary command in terms of using the words in oral form; (4) able to cover all students with different learning style, because there is no significant difference of vocabulary command among visual, auditory, and haptic students after they were taught by the method. In addition, students have good perception of the Vocabulary-based Integrated Activities. Key words: Vocabulary-based Integrated Activities, Vocabulary Command Learning Style